(untitled) (Baghdad Science Journal, 2012)
This study includes replication and attenuation of foot and mouth disease virus type O which isolated from infected calves. Many passages for the virus in chick-Embryo were established as a substitute method to the tissue culture which is highly caustic in contrast to the chick embryo. The virus passed ten consequent passages which lead to the reduce of the titer of the virus from 106.53 TCID50/ 0.1 ml in cattle testis tissue culture to 103 TCID50/ 0.1 ml. the pathogenecity of attenuated FMD virus were also studied in both chick-embryo and guinea pigs. Using agar gel diffusion test precipitation antibodies was detected in guinea pig serum after 14 and 21 days post exposure to the attenuated virus. The inoculated guinea pig group with the chick-embryo attenuated virus appear resistance to the challenge virus. The result suggested the efficacy of attenuation of foot and mouth disease virus by using chick-embryo system for immunization against this disease on the level of laboratory Animal.